Tumpang Tindih Kewenangan Penyidikan Badan Narkotika Nasional Dengan Kewenangan Penyidikan Kepolisian Republik Indonesia - M. Sahid (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2018)
Authority to conduct criminal investigations of narcotic regulated under Law No. 35 of2009 on Narcotics, namely article 81 of the law. Dibeikan investigative authority to thenational drug agencies and the police of the republic of Indonesia. With the division ofthe investigative authority of overlap and multiple interpretations of article 81 of LawNo 35 of 2009 on Narcotics. This paper aims to analyze the rules of authority narcoticsinvestigation of criminal offenses. This paper is based on research using the normativeapproach to law (statute approach) and the conceptual approach (conceptualapproach). The results showed that the regulation of narcotic crime investigationauthority should be clarified and given limit, so in practice the rule of law is not a clashof authority between the National Narcotics Agency to police the Republic of Indonesia.As well as law enforcement agencies in carrying out their duties effectively and goes inaccordance with the criminal justice system.